Arqueologia, História e Etnografia da Pesca: Pesqueiras e Tradição da Pesca em Ortiga (Rio Tejo, Mação) - Filipe, João de Matos; Lino, Jaisson Teixeira; Cura, Sara; Miranda, Antonio Luiz (Trabalhos de Antropologia e Etnologia, 2020)
The article presents in potential mode a first approximation to the study of Ortiga “pesqueiras” (fishery structures) in the Council of Mação under the archaeological, ethnographic, heritage and historical perspectives. The “pesqueiras” are architectural structures mostly composed of lithological material used in fishing activities and having a large occurrence in the area of the study. Dated since at least the sixteenth century, it is proposed here an initial exploration of the possibilities of interdisciplinary research, which can combine different areas of knowledge, thus contributing to a better understanding of the processes of origins, use and abandonment of these structures.